Evaluasi Layanan Sistem Informasi GO PPU Menggunakan Metode Pieces Framework Pada Disdukcapil Penajam - Ilda Ilda; Joy Nashar Utamajaya; Erlin Setyaningsih (JURIKOM (Jurnal Riset Komputer), 2022)
The Population Administration and Civil Registration Services provided by the Government to the Community are actually the result of thinking that follows the current relevant era. Along with the development of modern times, the Dukcapil District Office. Penajam Paser Utara presents innovations in public services provided through the GO PPU application. The involvement of the GO PPU application in public services in the field of population administration in North Penajam Paser Regency is the result of research from the previous population system. Therefore, the researcher tries to find out the performance system with the PIECES framework method which has six indicators of Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. The purpose of this study is to determine the main purpose of the agency to satisfy users of the service. By using PIECES as a tool to analyze the system, a detailed and comprehensive system will receive special attention, so that the strengths and weaknesses of the system can be known to later be used as a reference for the company's progress in the future. 98, it can be categorized as users who feel SATISFIED with the GO PPU information system service